Live-vaccinia virus encapsulation in pH-sensitive polymer increases safety of a reservoir-targeted Lyme disease vaccine by targeting gastrointestinal release. Issue 38 (31st August 2016) - Kern, Aurelie; Zhou, Chensheng W.; Jia, Feng; Xu, Qiaobing; Hu, Linden T.
Highlights: Reservoir-targeted vaccination is a promising method for preventing Lyme disease. Virally vectored vaccines are highly immunogenic but pose an exposure risk for humans. Coating with a pH-sensitive polymer targets gastrointestinal release of the virus. Polymer coatings increase safety of vaccinia vaccines by preventing unwanted exposure. Encapsulation with a pH sensitive polymer does not reduce efficacy of the vaccine. Abstract: The incidence of Lyme disease has continued to rise despite attempts to control its spread. Vaccination of zoonotic reservoirs of human pathogens has been successfully used to decrease the incidence of rabies in raccoons and foxes. We have previously reported on the efficacy of a vaccinia virus vectored vaccine to reduce carriage of Borrelia burgdorferi in reservoir mice and ticks. One potential drawback to vaccinia virus vectored vaccines is the risk of accidental infection of humans. To reduce this risk, we developed a process to encapsulate vaccinia virus with a pH-sensitive polymer that inactivates the virus until it is ingested and dissolved by stomach acids. We demonstrate that the vaccine is inactive both in vitro and in vivo until it is released from the polymer. Once released from the polymer by contact with an acidic pH solution, the virus regains infectivity. Vaccination with coated vaccinia virus confers protection against B. burgdorferi infection and reduction in acquisition of the pathogen by naïve feeding ticks.